Modeling and designing a Listeria monocytogenes control strategy for dry-cured ham taking advantage of water activity and storage temperature. (July 2020) - Serra-Castelló, Cristina; Jofré, Anna; Garriga, Margarita; Bover-Cid, Sara
Abstract: Dry-cured ham is a shelf-stable product that can be contaminated with Listeria monocytogenes due to post-processing operations, compromising the compliance of zero tolerance policies (e.g. US Listeria rule). The present study quantifies the behavior of L. monocytogenes in sliced Spanish dry-cured ham of different water activity (aw ) during storage at different temperatures. Inactivation kinetics were estimated by fitting primary models to the experimental data. The effect of temperature and aw on kinetic parameters was characterized through secondary polynomial models. L. monocytogenes viability decreased in all the assayed conditions, confirming that dry-cured ham is not only listeriostatic but listericidal. The fastest and highest reductions were observed at 25 °C, with 1 Log reduction after 6 and 9 days in Iberian and Serrano ham respectively. The work provides scientifically-based data and models to design a low-cost control measure based on a corrective storage as a post-lethality treatment to enhance the accomplishment of zero-tolerance requirements. Highlights: Dry-cured ham is not only listeriostatic, it may be listericidal. Listericidal effect was quantified as a function of aw and storage temperature. Iberian ham type favors an early inactivation of L. monocytogenes. A low-cost control measure is proposed as a post-lethality treatment.